2017
DOI: 10.1200/jco.2017.35.15_suppl.e15744
|View full text |Cite
|
Sign up to set email alerts
|

FOLFIRINOX versus gemcitabine nab-paclitaxel for advanced pancreatic cancer: KU Cancer Center experience.

Abstract: e15744 Background: FOLFIRINOX (FFN) and Gemcitabine plus nab-paclitaxel (GN) have been established as first line chemotherapy in advanced pancreatic cancer (PC). But there is no head-to-head randomized trial data available to support preferable first line choice between these two regimens. Methods: We retrospectively evaluated 154 chemotherapy-naïve locally advanced and metastatic PC patients treated with FFN or GN at KU Cancer Center between January 2011 and November 2016. FFN consisted of Oxaliplatin 85mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In five of these studies, the DCR was numerically greater with nab-P/G. 25,29,37,39,46 Overall, one study (patients with mPC) reported numerically greater DCR with FOLFIRINOX. 19…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In five of these studies, the DCR was numerically greater with nab-P/G. 25,29,37,39,46 Overall, one study (patients with mPC) reported numerically greater DCR with FOLFIRINOX. 19…”
Section: Resultsmentioning
confidence: 96%
“…Patients who received nab-P/G were treated for a median of 95 to 261 days versus 91 to 252 days with FOLFIRINOX. 11,20,23,28,29,37,39,40,42,47…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found a total of 493 publications in the electronic databases. A total of 16 studies including 3813 patients (2123 and 1690 of whom were treated with GEM-NAB and FOLFIRINOX respectively), were finally selected for inclusion after exclusion of duplicates and other non-pertinent papers [3,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20]. Fourteen were retrospective case series and two were cohort-studies.…”
Section: Resultsmentioning
confidence: 99%